Knuckle pads/Dermatitis artefacta. - Urbina, F.; Espinoza, X.; Sudy, E. (European Journal of Pediatric Dermatology, 2004)
Fingerpads are localized, benign, skin thickenings overlying the dorsal aspect of the digits. Single or multiple, they may vary from 0.5 to 1 centimeter in diameter, being hyper- or hypopigmented.